Knowledge co-creation in arts universities: the role of entrepreneurial mindset and communities of practice - Kristina Kuznetsova-Bogdanovitsh; Anna Maria Ranczakowska (European Journal of Cultural Management and Policy)
This article examines how an entrepreneurial mindset can act as a facilitator of knowledge management and co-creation within arts universities through the lens of Communities of Practice (CoPs). While entrepreneurial education in the arts is often framed as means to economic ends, we argue that its role extends significantly further. By integrating the entrepreneurial mindset into CoPs—where students, educators, and industry professionals collaboratively engage—arts universities can transform into dynamic learning organizations that align individual development with institutional knowledge creation. However, tensions arise within the CoPs when entrepreneurial education clashes with core artistic identities. Drawing on qualitative data from two European universities, this study critically examines the potential of entrepreneurial mindset for managing these tensions through the SECI model of knowledge management. Our findings reveal that when positioned as a tool for knowledge co-construction entrepreneurial mindset can facilitate alignment of students’ artistic values leading to both individual empowerment and institutional evolution.